Communicative-Based Short Video Design in Learning Maharah Kalam at Madrasah Aliyah - Nafiah, Annisatul Qolbi Qurrul (JURNAL IJ-ATL, 2024)
This study aims to develop and evaluate the effectiveness of communicative-based short videos as learning media for Maharah Kalam at Islamic High School State. The specific objectives of this research include: (1) describing the needs of teachers and students towards the use of communicative-based short videos, (2) designing short video-based learning media design, (3) evaluating the validity of learning media through expert testing, and (4) measuring the effectiveness of media in improving students' speaking skills. This research uses the Research and Development (R&D) method by adapting the Borg and Gall steps which are simplified into five stages: identification of potential and problems, data collection, product design, product validation, and product revision. Data were collected through interviews, observations, and questionnaires. Data analysis techniques were carried out by triangulating sources for qualitative data, as well as data validity tests for quantitative data. The results showed that the need for video-based media in learning Maharah Kalam was very high, with the average score of the student needs questionnaire reaching 76.09%. The short video design was developed using the VlogNow application with a communicative approach involving preparation, implementation, and evaluation stages. Material expert validation scored 87.5%, while media expert validation scored 88.3%, both in the valid category. After the product revision, this learning media proved to be effective in improving students' speaking skills. Therefore, this media can be used as a reference for educators in developing technology-based learning methods that are more communicative and interactive.